2016
DOI: 10.1038/srep38496
|View full text |Cite
|
Sign up to set email alerts
|

Two genomic regions associated with fiber quality traits in Chinese upland cotton under apparent breeding selection

Abstract: Fiber quality is one of the most important agronomic traits of cotton, and understanding the genetic basis of its target traits will accelerate improvements to cotton fiber quality. In this study, a panel comprising 355 upland cotton accessions was used to perform genome-wide association studies (GWASs) of five fiber quality traits in four environments. A total of 16, 10 and 7 SNPs were associated with fiber length (FL), fiber strength (FS) and fiber uniformity (FU), respectively, based on the mixed linear mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…Two cultivars with significantly different fiber lengths (TM-1, with longer fibers, and kenN27–3, with shorter fibers) were chosen to explore the function of GhPELs in fiber development [ 34 ]. The expression of 7 genes ( GhPEL4_At , GhPEL48_Dt , GhPEL30_At , GhPEL68_Dt , GhPEL76_Dt , GhPEL38_At , and GhPEL53_Dt ), most of which exhibit higher expression in fiber than other organs, was analyzed in 10 DPA, 15 DPA, 20 DPA and 30 DPA fibers of TM-1 and kenN27–3.…”
Section: Resultsmentioning
confidence: 99%
“…Two cultivars with significantly different fiber lengths (TM-1, with longer fibers, and kenN27–3, with shorter fibers) were chosen to explore the function of GhPELs in fiber development [ 34 ]. The expression of 7 genes ( GhPEL4_At , GhPEL48_Dt , GhPEL30_At , GhPEL68_Dt , GhPEL76_Dt , GhPEL38_At , and GhPEL53_Dt ), most of which exhibit higher expression in fiber than other organs, was analyzed in 10 DPA, 15 DPA, 20 DPA and 30 DPA fibers of TM-1 and kenN27–3.…”
Section: Resultsmentioning
confidence: 99%
“…Using a map of single nucleotide polymorphism (SNP) markers, one fiber length hotspot on Chr 5 carrying three QTLs was observed (Li et al 2016). Additionally, four potential candidate genes for fiber length on Chr Dt7 were found using genotyping by sequencing by genome-wide association studies (GWAS) (Su et al 2016). Previous studies indicated that the RIL population and its two BCF 1 populations which derived from the same parents increased the power of QTL detection in cotton (Shang et al 2016d; Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the development of CottonSNP63K (Hulse-Kemp et al, 2015) and CottonSNP80K (Cai et al, 2017) arrays has allowed genetic mapping, genomic selection, genome-wide association studies, and an understanding of genomic diversity among Gossypium breeding populations. Common QTLs related to fiber quality in different environments identified through SNP markers can be deployed as a priority for fine mapping and candidate genes identification Su et al, 2016;Tan et al, 2018).…”
Section: High-throughput Sequencing Techniques For Fiber Quality Traitsmentioning
confidence: 99%